Databook of antiblocking, release and slip additives - Wypych, Anna, 1937- (ChemTec Publishing, 2013)
The Databook of Antiblocking, Release, and Slip Additives contains detailed information on over 300 important additives for polymers - additives which are used to minimize adhesion, aid separation and enhance processing and end-applications for polymers. The variety of additives available makes this databook an invaluable source of information for industry, research, and academia. Each additive is presented with data in the following categories: General Information; Physical Properties; Health and Safety; Ecological Properties; and Use and Performance. The Databook includes a large amount of data, from state, odor, and color to autoignition temperature and probability of biodegradation. Recommendations are given for specific products, processing methods and mold materials, and an assessment is given for each additive's features and benefits, enabling practitioners to select the correct additive for each situation. Contains the most extensive data available on a large number of antiblocking, release and slip additives for polymersFeatures 130 data fields for each additive, divided into the following categories: General Information, Physical Properties, Health and Safety, Ecological Properties, and Use and PerformanceIncludes an assessment of benefits and properties of each additive, recommended dosages and processing methods.